أنواع تراجم معاني القرآن الكريم والحكم عليها (Types of Translations of the Meanings of the Noble Qur’an and its Evaluation) - شاشوار هاشاني برات; منصور محمد سعد الدين (Journal of Islam in Asia (E-ISSN 2289-8077), 2021)
تهتم المقالة ببيان أنواع تراجم معاني القرآن الكريم إلى اللغات الأجنبية وإيضاح المنهج الذي يجوز اتباعه في الترجمة، والمنهج الذي لا يجوز. كما تركز المقالة على ذكر أقوال العلماء حول حكم ترجمة معاني القرآن الكريم إلى اللغات الأجنبية، والأدلة التي استدلوا بها. وتهدف المقالة إلى بيان مناهج ترجمة معاني القرآن الكريم إلى اللغات الأجنبية. كما تهدف إلى بيان منهج الترجمة الذي يجوز اتباعه شرعا والمنهج الذي لا يجوز شرعا ولا يمكن تحقيقه حسب الشروط والضوابط المطلوبة شرعا. ويستخدم الباحث المنهج التاريخي والمنهج المقارن. توصل البحث إلى أنّ هناك نوعين من الترجمة: الترجمة الحرفية التي لا تجوز شرعا، والترجمة المعنوية التي تجوز شرعا. الكلمات المفتاحية: الترجمة، القرآن، الألفاظ، المعاني. Abstract The article is concerned with the types of translation of the meanings of the Noble Qur’an into foreign languages. It helps the researcher to understand the approach that may be followed, and the approach that may not, in such translations. The article also focuses on mentioning the opinions of scholars about the ruling on translating the meanings of the Noble Qur’an into foreign languages, and the evidence they used. The article aims to explain the methods of translating the meanings of the Noble Qur’an into foreign languages. It also aims to show the translation approach that may be legally followed. And the approach that is not legally permissible and cannot be achieved according to the conditions and controls required by sharia law. The researcher uses the historical method and the comparative method. The research found that there are two types of translation; literal translation, which is not permissible by sharia law, and the semantic translation that is permissible by sharia law. Keywords: Translation, Qur’an, Words, Meanings.